2011
DOI: 10.1007/s00244-011-9713-8
|View full text |Cite
|
Sign up to set email alerts
|

Using Legacy Data to Relate Biological Condition to Cumulative Aquatic Toxicity in the Willamette River Basin (Oregon, USA)

Abstract: In the Willamette River Basin (Oregon, USA), various residential, municipal, industrial, and agricultural activities produce physical, biological, and chemical stressors that may impinge on the basin's aquatic ecosystems. For > 30 years, numerous water-quality and biological-condition data have been accumulated by often disparate monitoring programs. This diagnostic analysis explored whether these legacy data could be used to correlate the presence of chemical stressors with biological condition impacts with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In addition, hydrological alterations used to support agricultural systems can reduce in stream flows and groundwater stores (Scanlon et al, 2007), attenuate flood pulses, and reduce riparian habitat (Poff et al, 1997) and native fish movement (Schlosser, 1995). Similarly, even seemingly small proportions of urban land cover (i.e., 10-20%; Allan, 2004) can lead to substantial increases in the amount of chemical and thermal pollution in rivers (Hope, 2012), and decreases in stream-channel habitat structure and biodiversity (Roy et al, 2003;King et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hydrological alterations used to support agricultural systems can reduce in stream flows and groundwater stores (Scanlon et al, 2007), attenuate flood pulses, and reduce riparian habitat (Poff et al, 1997) and native fish movement (Schlosser, 1995). Similarly, even seemingly small proportions of urban land cover (i.e., 10-20%; Allan, 2004) can lead to substantial increases in the amount of chemical and thermal pollution in rivers (Hope, 2012), and decreases in stream-channel habitat structure and biodiversity (Roy et al, 2003;King et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that some of surface waters and surrounding environments were contaminated with different insecticides (Arjmandi et al, 2010;Bagheri et al, 2000;Ghassempour et al, 2002;Rahiminezhhad et al, 2009;Tarahi Tabrizi, 2001). The continuous presences of insecticides are the consequence of application (timing, rate, frequency) and the rainfall during the application period (Lydy and Austin, 2004; U.S.A. EPA, 2005;Bouldin et al, 2007;Mast et al, 2007;Echols et al, 2008;Vryzas et al, 2009;Werimo et al, 2009;Ding et al, 2011;Hope, 2012). Although monitoring the presence of insecticides in surface water and ground water are generally poor in much of the world and especially in developing countries, the effect of these pollutants on aquatic animals' health frequently was investigated (Chambers et al, 2002;Richards and Kendall, 2002;Lam and Wu, 2003;Scott and Sloman, 2004;Cengiz, 2006;Sun and Chen, 2008;; Banaee et al, 2011; Banaee and Ahmadi, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The chemical components become diluted in environmental media that already contain other chemicals, including pesticides. For example, in Oregon's Willamette River Basin, only 3.6% of surface-water samples collected during 1994-2010 contained only a single detected chemical; over 50 pesticide mixtures of two to six pesticides each were found in the remaining samples (Hope 2012). Nationally, more than 6,000 unique mixtures of five pesticides were detected in agricultural streams (Gilliom et al 2007).…”
Section: Environmental Mixturesmentioning
confidence: 99%